PENGARUH PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. KALTIM BANUA ETAM SANGATTA - Amoz Rombo; Riduansah; Irma (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2020)
This study aims to identify how much influence the safety and health of employees so that it affects the performance of employees at PT. East Kalimantan Banua Etam District, Sangatta. This study uses descriptive analysis with a quantitative approach. The population in this study were employees of PT. Kaltim Banua Etam, Sangatta using multiple linear regression analysis with the help of SPSS version 26 program. The results showed that the variables of occupational safety and health had a positive and significant effect on employee performance